INTERNALISASI NILAI-NILAI ISLAM DALAM MEMBENTUK GENERASI AQIL BALIGH DI SMPIT AL WAKIL - Fatchur, Imam; Zain, Biqi Asshafah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the process of internalizing Islamic values in forming the aqil baligh generation at SMPIT Al Wakil Tulakan Pacitan. This research uses a qualitative approach with a case study design. Data collection techniques were carried out through observation, interviews, and documentation of various educational activities in the school environment. The results show that the internalization of Islamic values is implemented through the integration of learning activities, religious habituation, and the strengthening of a religious school culture. The main strategies include teacher role modeling, habituation of religious activities, and the creation of a religious educational environment. In addition, the school develops a character development model based on the concept of aqil baligh through six indicators: active, survive, resilient, mukallaf, wise, and civilized. This process contributes to developing students’ religious awareness and moral responsibility in carrying out religious obligations.